TRANSDERMAL PATCH FORMULATION OF NUTMEG EXTRACT WITH HPMC (HYDROXY PROPYL METHYL CELLULOSE) AND EC ETHYL CELLULOSE (EC) AS POLYMERS - Suci Rahmawati; Yetti Purnama; Kurnia Dewiani; Oky Hermansyah; Nizella Syaenri; Sari Surya Guma Sri; Elda Jumiati (Poltekkes Kemenkes Bengkulu, 2023)
Nutmeg seed extract (Myristica fragrans Houtt) contains myristicin which have been an anti-inflammatory effect. Nutmeg seed extract is formulated into transdermal patch to avoid the first pass effect. This study was aimed to determine the best nutmeg extract patch transdermal formula using HPMC and EC as polymers. In this study, nutmeg extract was obtained by kinetic maceration method using 96% ethanol. The patch formula was designed into two formulas that have different types of polymer with a concentration of 4.5%, namely FP1 with HPMC polymer and FP2 with EC polymer. Patches that were evaluated for physical properties included organoleptics, weight uniformity, patch thickness, folding resistance test, drying shrinkage, absorbency test and pH. The results showed that FP1 had good organoleptic (elastic shape and even brown color); Uneven weight and thickness (SD < 0.05); Folding endurance test of 300 X; drying shrinkage 25%; absorption capacity of 8.1% and pH 6. Meanwhile, FP2 appears to have poor organoleptic properties (wrinkled shape and uneven brown color; uneven weight (SD < 0.05); uneven thickness (SD > 0.05); test folding resistance of 100 X, drying shrinkage 22.5%; absorption capacity of 20.2% and pH 6. In this study it can be concluded that FP1 with HPMC was the best formula for transdermal patch containing ethanol extract of nutmeg seeds.